The Effect of Technology on Trafficking in Persons After the Covid-19 Pandemic - Heni Susanti; Lidya Chabelita Silaban; Evi Yanti; Yusramiza Md Isa; Syafrinaldi Syafrinaldi (Proceeding International Conference on Malay Identity, 2022)
The purpose of this research is to know and understand the implementation of law enforcement against the Crime of Trafficking in Persons, as well as how the influence of digitalization in carrying out law enforcement against the Crime of Trafficking in Persons in the Riau Regional Police (Riau Regional Police).The method used in this research is empirical legal research by conducting research on the role of the Riau Regional Police (Riau Regional Police) in law enforcement, with data collection tools, namely interviews. The nature of this research is descriptive in nature, that is, it provides a clearer picture by revealing the problems and conditions as they are.From the results of the research it is known that the Crime of Trafficking in Persons is a type of crime that is worrying in Riau Province, dominated by the mode of illegal migrant workers. Riau Province is used by trafficking syndicates to serve as a transit area before sending victims to their destination, namely Malaysia. The Riau Regional Police (Polda Riau) as a law enforcement agency carries out its duties in prevention, law enforcement and countermeasures. The influence of digitalization on law enforcement on trafficking in persons has made this crime more prevalent with a more sophisticated modus operandi. Keywords: Trafficking in Persons, Digitalization, Post Pandemic Covid 19 Abstrak Tujuan penelitian ini adalah mengetahui dan memahami pelaksanaan penegakan hukum terhadap Tindak Pidana Perdagangan Orang, serta bagaimana pengaruh digitalisasi dalam melaksanakan penegakan hukum terhadap Tindak Pidana Perdagangan Orang di Kepolisian Daerah Riau (Polda Riau).Metode yang digunakan dalam penelitian ini adalah penelitian hukum empiris atau empirical legal research dengan melakukan penelitian terhadap peranan Kepolisian Daerah Riau (Polda Riau) dalam penegakan hukum, dengan alat pengumpulan data yaitu wawancara. Sifat penelitian ini adalah bersifat deskriptif, yaitu memberikan gambaran lebih jelas dengan mengungkapkan masalah dan keadaan sebagaimana adanya.Dari hasil penelitian diketahui bahwasanya Tindak Pidana Perdagangan Orang merupakan jenis tindak pidana yang mengkhawatirkan di Provinsi Riau, didominasi dengan modus pekerja migran ilegal. Provinsi Riau digunakan sindikat perdagangan orang untuk dijadikan sebagai daerah transit sebelum memberangkatkan korban ke daerah tujuan, yaitu Malaysia. Kepolisian Daerah Riau (Polda Riau) sebagai lembaga penegak hukum menjalankan tugasnya dalam upaya pencegahan, penegakan hukum dan penanggulangan. Adnya pengaruh digitalisasi terhadap penegakan hukum perdagangan orang menjadikan kejahatan ini semakin marak terjadi dengan modus operandi yang lebih canggih. Kata kunci : Perdagangan Orang, Digitalisasi, Pasca Pandemi Covid 19